Reference centiles for maternal placental growth factor levels at term from a low-risk population. (October 2019) - Dunn, Liam; Sherrell, Helen; Bligh, Larissa; Alsolai, Amal; Flatley, Christopher; Kumar, Sailesh
Abstract: Introduction: Placental growth factor (PLGF) is a biomarker of placental function. The aim of this study was to define reference ranges for maternal PLGF levels in a normotensive cohort ≥36 + 0 weeks. Method: Prospective observational data from Mater Mothers' Hospital, Brisbane. PLGF levels were measured in women at ≥36 + 0 weeks with singleton, non-anomalous pregnancies. Women with hypertension and fetal growth restriction were excluded. PLGF (pg/mL) was assayed using DELFIA® Xpress (PerkinElmer Inc). The Generalised Additive Model for Location, Shape and Scale (GAMLSS) method was used for the calculation of gestational age-adjusted centiles. Data analysis was performed with Stata 13 (StataCorp, LLC) and R software (R Foundation for Statistical Computing, Vienna, Austria). In all women, PLGF was measured within 2 weeks of delivery. Results: The study cohort comprised of 845 women (36 weeks n = 73, 37 weeks n = 230, 38 weeks n = 214, 39 weeks n = 172, 40 weeks n = 115, 41weeks n = 41). PLGF levels were negatively correlated with gestational age (r = −0.20, p < 0.001). Median PLGF levels dropped significantly from 36 weeks to 41 weeks (169.0 pg/mL to 96.6 pg/mL, p < 0.001). Gestational age specific maternal PLGF centiles were reported using fractional polynomial additive term and Box-Cox t distribution. PLGF did not perform adequately as a predictive test for adverse perinatal outcomes (AUC <0.6). Discussion: We have created gestational centile reference ranges for maternal PLGF from a normotensive cohort. These novel data suggest maternal PLGF levels decline ≥36 + 0 weeks. The utility of PLGF as a predictor of adverse perinatal outcomes at term, should be further investigated with clinical trials. Highlights: Reference ranges for maternal PLGF in normotensive term cohort. Maternal PLGF falls significantly after 36 weeks gestation. At term, PLGF did not predict adverse perinatal outcomes adequately.